Synergistic effect of hyperforin and paclitaxel on growth inhibition, apoptotic mediator activation in MCF-7 human breast cancer cells. Issue 1 (1st January 2021) - Barathan, Muttiah; Zulpa, Ahmad Khusairy; Mee Hoong, See; Vellasamy, Kumutha Malar; Vadivelu, Jamuna
Abstract : The role of hyperforin in combination anticancer therapy remain unknown. In this study, several doses of combination treatment (paclitaxel and hyperforin) were introduced to the Michigan Cancer Foundation (MCF)-7 cell culture for 24 h. The effectiveness of the drug's combination effect was determined by the combination index (CI)followed by the anticancer effect through apoptosis, reactive oxygen species (ROS), lactate dehydrogenase (LDH) and caspase 8 assays. It was found that combined doses of paclitaxel (7, 6, 5, 4 µg/mL) and doses of hyperforin (1, 2, 3 and 4 µg/mL) enhanced synergistic growth inhibitory effect. (Hy: 4 µg/mL & Pa: 4 µg/mL) was selected as suitable dose with lowest CI and it significantly induced changes to MCF-7 cell morphology and led to apoptosis with increased in the high level of ROS, LDH and caspase 8 compared to singly treated hyperforin. This study provides the basis for elucidation of combination of hyperforin and paclitaxel on animal models.